Comparative Study of Different Vegetable Oil during turning in terms 0f Cutting Force and Power Consumption. - Ghuge, Nilesh C.; Mahalle2, Dr.Ashish M. (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
Cutting fluids used in machining are environment hostile, noxious and expensive. They may produce several environmental problems such as polluting the water resources, damaging the soils affecting the operators health. Now day’s researchers are trying to eliminate the poisonous fluids without affecting the performance.Curiosity in vegetable oil is rising Minimum quantity lubrication system uses very minute amount of cutting fluid. Combining of MQL and vegetablemay result into less amount of environment friendly cutting fluid to improve the output .This save money as well as protect the environment. This paper concentrates on fabrication of low cost, simple MQL system and to evaluate performance of various vegetable oil based on cutting forces, temperature. The experimental results shows that vegetable oil outpaces the mineral-based fluid